Ecopolyol Production from Industrial Cork Powder via Acid Liquefaction Using Polyhydric Alcohols - Soares, Belinda; Gama, Nuno; Freire, Carmen; Barros-Timmons, Ana; Brandão, Inês; Silva, Rui; Pascoal Neto, Carlos; Ferreira, Artur (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2014)
Ecopolyol production from acid liquefaction of cork powder was studied for the first time using PEG 400 and glycerol as liquefaction solvents in the presence of sulfuric acid at moderate temperature and atmospheric pressure. The effect of the temperature, concentration of catalyst, and time on the liquefaction yield has been investigated using a fixed set of reaction conditions namely, a liquefaction solvent mixture/cork powder ratio of 5/1 and a solvent mixture PEG 400/glycerol ratio of 90/10. The full-factorial design of experiments (DOE) 23 was applied to obtain an optimized set of liquefaction conditions aiming at minimizing the residue content. The minimum residue contents experimentally obtained in this study were 29 wt %, related to cork powder, which were achieved at 150 C, 4 wt % of sulfuric acid, and 60 min. This value corresponds to 5 wt % of residue per total mass of reaction product. The polyols obtained under optimal conditions present similar characteristics (hydroxyl number value 219 mg(KOH)/g(polyol) and viscosity 2875 cP, at 25 degrees C) to those of petroleum-based polyols typically used in the polyurethane foam industry.
Keywords: Glycerol; Liquefaction process; PEG 400; Polyols

Production of biomaterials from cork: Liquefaction in polyhydric alcohols at moderate temperatures - Yona, Arnaud Maxime Cheumani; Budija, Franc; Kričej, Borut; Kutnar, Andreja; Pavlič, Matjaž; Pori, Pavel; Tavzes, Črtomir; Petrič, Marko (Industrial Crops and Products, 2014)
The aim of this study was to develop polymers in a liquid solution, from renewable bio-resources, usable as intermediate materials in the preparation of plastics, adhesives or coatings. The liquefaction of cork with glycerol was investigated at 150◦C, 180◦C, and 200◦C under acidic (sulphuric acid) or alkaline conditions (sodium hydroxide). Cork appears as a two-component material, containing suberin and lig- nocelluloses. In the presence of sulphuric acid, only the liquefaction of the lignocellulosic components was achieved, leading to liquefaction yield of less than 47% at all investigated conditions. The inverse phenomenon was observed with sodium hydroxide. Suberin was almost completely liquefied, but an increase of temperature and/or sodium hydroxide content was necessary to improve the liquefaction of lignocelluloses. Addition of polyethylene glycol to glycerol to a certain extent caused the conversion of suberin under acid conditions leading to liquefaction yield up to 93%. Therefore, it was demonstrated that it is possible to use cork dust, a less valuable by-product, for the production of various basic chemicals and/or polymers with a high added value
Keywords: Cork; Glycerol; Liquefaction; Polyethylene glycol; suberin

Methanolysis of bark suberins: analysis of glycerol and acid monomers - Graça, J; Pereira, Helena (Phytochemical Analysis, 2000)
The depolymerization and subsequent analysis of cork suberins from the outer barks of Pseudotsuga menziesii and Quercus suber was performed using a simpliﬁed methanolysis procedure. The amount of sodium methoxide catalyst was maintained at 20–30 mM and the methanolysis mixture was submitted to trimethylsilyl derivatisation and used directly for gas chromatographic analysis, allowing simultaneous quantiﬁcation of glycerol and long-chain monomers. Response factors for glycerol, ferulic acid and one saturated homologue representing each of the suberinic families (i.e. the 1-alkanols, 1-alkanoic acids, vhydroxyacids and a,v-diacids) were determined. Effective depolymerization of suberin was checked using the infrared specta of the residues after methanolysis. Glycerol is a major constituent of the suberins from P. menziesii (26% of total) and from Q. suber (14%). In both suberins, a,v-diacids are dominant, i.e. 54% of the long-chain monomers in P. menziesii (mostly saturated C16-C22 homologues and the C18 unsaturated diacid), and 53% in Q. suber (mostly the C18 unsaturated diacid and mid-chain oxygenated (epoxide and vic-diol) derivatives). In P. menziesii epoxyacids are absent. The importance of glycerol and a,v-diacids as suberin monomers supports a polymeric structure based on their successive esteriﬁcation.
Keywords: Cork; Glycerol; Methanolysis; monomer composition; Pseudotsuga menziesii; Quercus suber; suberin

Cork Suberin: A Glyceryl Based Polyester - Graça, José; Pereira, Helena (Holzforschung - International Journal of the Biology, Chemistry, Physics and Technology of Wood, 1997)
Total depolymerization of cork from the cork oak (Quercus suber L.) by using a sodium methoxide catalysed methanolysis solubilized 53.2 % of the material, including 5.2 % of glycerol, 48,0 % of suberinic fatty acids and alcohols and minor amounts of ferulic acid. A very mild depolymerization using calcium oxide treated methanol, which solubilized only 2.0% of the cork material was studied by GC-MS. In the solubilized material, the total amount of aliphatic acids was 43.8 % (including alkanoic acids 4.0%. ω-hydroxyacids 13.2% and α,ω-diacids 26.6%), of 1-alkanols 2.1 % and of monoacylglycenols 32.1%. It was possible to identify 1-monoacylglycerols and 2-monoacylglycerols of alkanoic acids (1,2%), ω-hydroxyacids (3.7 %) and α,ω-diacids (22.8 %). It is proposed that suberin is a glyceryl based polymer and that its insoluble character is given, at least in part, by the cross-linking of dicarboxylic fatty acids with glycerol. The term suberin should be used for this aliphatic polyester component of the cell wall.
Keywords: Cork; Glycerol; Monoacylglycero; Quercus suber; suberin

Suberina: o polímero responsá vel pelas propriedades da cortiça - Graça, José; Pereira, Helena (II Congreso Forestal Español, 1997)
The macromolecular structure of suberin, the biopolymer mainly responsable for cork properties, is dicussed. The link of the suberinic aliphatic acids to glycerol is presented, supporting the hypothesis that suberin is a glyceridic polyester. The linkage of this aliphatic part, through ferulic acid, to the aromatic part, and the similarities of the later to lignin, are discussed. K.W.:
Keywords: Cork; ferulic acid; Glycerol; suberin